THE USE OF CAMTASIA VIDEO EDITOR TO IMPROVE THE STUDENTS’ PRONUNCIATION SKILL AT ENGLISH STUDY PROGRAM IAIN METRO LAMPUNG - Much Deiniatur (INOVISH JOURNAL, 2019)
This research is aimed to know whether Camtasia could improve the students’ pronunciation skill at the first semester English Education Study Program IAIN Metro Lampung in the Academic Year of 2018/2019. This research is carried out on the subject of English Phonology.The design of this research was a classroom action research. It was conducted in two cycles. The data collection method in this research was observation, test, documentation, and field note. the cycle I the average score of pre-test cycle I was 60, 3 and the average of post-test in cycle I was 64, 5. In the post-test in cycle II the average score was 75, 8. There are some progresses after being given treatment through video produce by camtasia. The students are very interested in following and doing the assignment given by the researcher. From the result of the discussion above, it can be conclude that the use of Camtasia can improve the students’ pronunciation skill at the first semester English Education Study Program IAIN Metro Lampung in the Academic Year of 2018/2019. Key words: Pronunciation, Camtasia, Video, Editor